Endocrinopathies by Oncological Immunotherapy - Scheinfeld, Ester Gabriela; Lovazzano, Soledad; Ramajo, María Fernanda (Revista del Hospital Italiano de Buenos Aires, 2020)
The relationship between immunity and cancer is complex. Tumor cells develop evasion mechanisms to the immune system responses. This ability allows their survival and progression. Immunotherapy has transformed cancer treatment by improving the immune response against tumor cells. This is achieved by blocking immune checkpoints with monoclonal antibodies against cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) and programmed cell death protein 1 and its ligand (PD-1 / PD-L1). Although the immune checkpoint inhibitors (ICIs) are well tolerated drugs, they have a profile of adverse effects known as immune-related adverse events (irAES). These involve diverse systems, including the endocrine glands. The most frequent endocrine immune-related adverse events are thyroid and pituitary dysfunction, autoimmune diabetes mellitus and primary adrenal insufficiency. The increasing knowledge of these irAES has led to effective treatment strategies with the corresponding hormonal replacement. The objective of this review is to recognize the incidence of these new endocrinopathies, the physiopathology, their clinical evaluation, and therapeutic management.
Keywords: immunotherapy; immune checkpoint inhibitors; immune-related adverse events(irAEs); endocrinopathies; adrenal insufficiency; hypophysitis; autoimmune diabetes; hypothyroidism; hyperthyroidism; thyroiditis